Key Factors for In-Store Smartphone Use in an Omnichannel Experience: Millennials vs. Nonmillennials - Ana Mosquera; Emma Juaneda-Ayensa; Cristina Olarte-Pascual; Jorge Pelegrín-Borondo (Complexity)
The in-store use of smartphones is revolutionizing the customer journey and has the potential to become an important driver in the omnichannel context. This paper aims at identifying the key factors that influence customers’ intentions to use smartphones in-store and their actual behavior and to test the moderating effect of age, differentiating between millennials and nonmillennials, as millennials are considered digital natives and early adopters of new technologies. We applied the UTAUT2 model to a sample of 1043 Spanish customers, tested it using structural equations, and performed a multigroup analysis to compare the results between the two groups. The results show that the model explains both the behavioral intention to use a smartphone in a brick-and-mortar store and use behavior. The UTAUT2 predictors found to be most important were habit, performance expectancy, and hedonic motivation. However, the study shows that the only difference between millennials and nonmillennials with regard to the use of smartphones in-store is the effects of behavioral intention and habit on use behavior. The study adds to the existing knowledge by providing evidence in support of the validity of UTAUT2 as an appropriate theoretical basis to explain effectively behavioral intention, specifically the in-store use of smartphones.